Expression of CD3 and CD79a cell markers in exfoliative and ulcerative skin lesions in dogs with leishmaniasis - Neto, Rafael Torres [UNESP]; Rodrigues, Marcela Marcondes Pinto [UNESP]; Amorim, Renée Laufer [UNESP]; Conceição, Lissandro Gonçalves; Luvizotto, Maria Cecília Rui [UNESP]; Franco, Sônia Regina Verde Silva (Universidade Estadual de Londrina, 2008)
Canine visceral leishmaniasis is an endemic infectious disease in some regions from São Paulo state and even though it is a systemic disease, in the dog, the main clinical sign is dermatological. Thirty dogs with positive results in serology (IFI) and parasitological exams (fine needle aspiration) for leishmaniasis from Araçatuba city were evaluated. They only showed dermatological signs and were divided in two groups, one with exfoliative (n=15) and other with ulcerative (n=15) lesions. There was significant statistical difference between CD3 and CD79a population in the same dermatological pattern, and with CD79a population between exfoliative and ulcerative patterns (p<0,05).
Imunomarcação de células CD3+ e CD79a+ nas lesões descamativas e ulcerativas de cães com leishmaniose
Keywords: Dog; Exfoliative dermatitis; Immunohistochemistry; Leishmaniasis; Ulcerative dermatitis